Enabling financial inclusion for the unbanked : in pursuit of a regulatory framework for mobile money in Uganda - OluSoyeju, Olufemi Olugbemiga (University of Pretoria, 2018)
Mini Dissertation (LLM)--University of Pretoria, 2017.